Classical dynamics: A contemporary approach - Jose, Jorge V.; Eugene J. Saletan (New York : Cambridge University Press, 2012)
"Recent advances in the study of dynamical systems have revolutionized the way that classical mechanics is taught and understood. Classical Dynamics: A Contemporary Approach is a new and comprehensive textbook that provides a complete description of this fundamental branch of physics." "It will be an ideal textbook for graduate students of physics, applied mathematics, theoretical chemistry, and engineering, and will also serve as a useful reference for researchers in these fields."--Jacket
Fundamentals of mechanics -- Lagrangian formulation of mechanics -- Topics in Lagrangian dynamics -- Scattering and linear oscillations -- Hamiltonian formulation of mechanics -- Topics in Hamiltonian dynamics -- Nonlinear dynamics -- Virigid bodies -- Continuum dynamics.
Includes bibliographical references (pages 656-662) and index.
Keywords: MECHANICS, ANALYTIC